Molecular regulation of glial inflammation in Parkinson's disease - De Miranda, Briana R., author; Tjalkens, Ronald, advisor; Kato, Takamitsu, committee member; Legare, Marie, committee member; Mykles, Donald, committee member (Colorado State University. Libraries, 2014)
Parkinson's disease (PD) is the most prevalent movement disorder that affects adults, the primary pathology of which includes the loss of dopamine producing neurons from the substantia nigra (SN) and inflammatory activation of immune mediators in the brain. Reactive astrocytes and microglia have been implicated in driving the progressive phase of dopamine neuron loss in PD, the result of which leads to worsening neurodegeneration over time that no current therapy can inhibit. A significant need exists for small molecule therapeutics that reach the CNS, decrease glial activation, and confer neuroprotection over the progressive phase of PD. A novel class of anti-inflammatory compounds, originally shown to have anticancer properties, are examined here as potential therapeutic agents to decrease glial inflammation in a progressive mouse model of PD. Derived from the condensation product of indol-3-carbinol produced in cruciferous vegetables, para-phenyl substituted diindolylmethanes or C-DIMs have been shown to induce orphan nuclear receptor family NR4A in several different cancer lines, and have reduced inducible nitric oxide synthase (NOS2) expression in primary murine astrocytes. In order to examine the neuroprotective benefit selected C-DIM compounds have on the survival of dopamine neurons during the inflammatory progressive phase of PD, several experimental studies were conducted, and reported here. The initial development of a method using immunofluorescent sereological counts of TH-positive neurons in the SN, resulted in the ability to measure early neuronal degeneration with sensitivity to small changes in neuron loss through design-based 3D modeling of the SN. Additionally, a pharmacokinetic analysis of four C-DIM compounds determined that structural variations changed the metabolism of these compounds in mice, however all C-DIMs tested were orally bioavailable, distributed to the brain, and displayed pharmacokinetic profiles equivalent to current PD therapies. Initial neuroprotective studies demonstrated that three of the selected C-DIMs are able to limit the progression of dopamine neuron loss from the SN after the onset of a lesion, in a progressive PD mouse model using 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP, 80 mg/kg) and the drug clearance inhibitor probenecid (250 mg/kg, expressed as MPTPp). A post lesion model was utilized in transgenic NF-κB-EGFP adult mice, where MPTPp treatment was given for 7 days (MPTPp7d) and animals were given either corn oil (vehicle) or one C-DIM (DIM-C-pPhOCH3, DIM-C-pPhOH, DIM-C-pPhCl) via daily oral gavage for the next 7 days (MPTPp14d). Further investigation into the mechanism by which CDIMs reduced dopamine neuron loss revealed that activation of microglia and astrocytes was reduced in the SN from MTPPp7d to MPTP14d in animals given daily oral gavage of the compounds, compared to corn oil control. NF-κB-EGFP intrinsic reporter detection of NF-κB expression was reduced in C-DIM treated animals compared to animals that received no treatment from MPTPp7d to MPTPp14d. Reduction in NF-κB related cytokines (TNF, IL-1α, IFNγ) were also seen after C-DIM treatment. As a final investigation into C-DIM mechanism of action, DIM-C-pPhCl was examined in the BV-2 microglia cell line treated with LPS to stimulate cytokine production. DIM-C-pPhCl treatment reduced the expression of inflammatory proteins such NOS2, TNFα, and IFNγ after LPS treatment, and its effectiveness was dependent on the nuclear receptor transcription factor NR4A2 (Nurr1). In addition, DIM-C-pPhCl treatment increased the amount of Nurr1 present at the NOS2 promoter, suggesting that it enhances the Nurr1-dependent transrepression of NF-κB, recently described as a novel mechanism in glial cells to reduce inflammatory protein and protect against the progression of PD.